STRUCTURAL PROCESSES IN THE LIGHT OF THE BACKLASH EFFECT - Délli Ribeiro Rodrigues, Marcos; Paula da Costa Ribeiro, Bruna; Ribeiro Linhares , Natália; Quirino Ribeiro, Ingrid (Revista Gênero e Interdisciplinaridade, 2023)
Currently, some disputes are so complex that they require an entire reform of the institutes involved in order to stop the violation of rights. In this approach, structural processes come into play, as a means of solving imbroglios of this complexity. However, there are obstacles to the effectiveness of judgments in the structural process, such as the backlash effect. Thus, the question is urgent: is it possible, even in the face of impasses, that the structural sentence generates positive effects in the world of facts? Based on doctrinal, jurisprudential and legislative studies, it is understood that the most appropriate solution for the case is the use of the dialogic sentence technique.